2005
DOI: 10.1021/jo050704x
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation with Trichloroacetimidates in Ionic Liquids:  Influence of the Reaction Medium on the Stereochemical Outcome

Abstract: [reactions: see text] The glycosylation with trichloroacetimidates derived from different glycopyranoses bearing a nonparticipating group at C-2 was explored in different ionic liquids as solvents. The stereoselectivity of the reaction was significantly affected by the reaction media and by the anomeric configuration of the donor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 16 publications
3
42
0
Order By: Relevance
“…The reactions proceeded at room temperature under mild conditions in these solvents, and the use of a Lewis acid catalyst could be avoided in some cases. [169] The "inverse procedure" developed by Schmidt and Toepfer in 1991 [170] often provided the desired glycosidation products when glycosidation reactions otherwise failed to give glycosides or when orthoesters tended to form. [103] In the inverse procedure, it is thought that acceptor molecules aggregate around the catalyst, and that an intramoleculartype glycosylation takes place on the approach of the donor.…”
Section: O-glycosyl Imidates With Electron-withdrawing Groupsmentioning
confidence: 99%
“…The reactions proceeded at room temperature under mild conditions in these solvents, and the use of a Lewis acid catalyst could be avoided in some cases. [169] The "inverse procedure" developed by Schmidt and Toepfer in 1991 [170] often provided the desired glycosidation products when glycosidation reactions otherwise failed to give glycosides or when orthoesters tended to form. [103] In the inverse procedure, it is thought that acceptor molecules aggregate around the catalyst, and that an intramoleculartype glycosylation takes place on the approach of the donor.…”
Section: O-glycosyl Imidates With Electron-withdrawing Groupsmentioning
confidence: 99%
“…Surprisingly, the use of α-trichloroacetimidate 5α derived from glucose as donor and 1 as acceptor, predominantly afforded the α-glycoside, albeit with a lower α/β ratio (85:15; see Table 1, Entry 6). Selectivity studies on glycosylation reactions with ionic liquids used as solvent were reported by Poletti [14] and Toshima, [15] with a nonparticipating group at the C-2 position. However, whereas triflate-based ionic liquids induced β-selectivity (presumably by coordination of the triflate counterion on the α-face of the glycosyl donor), no influence of the hydrophobic, noncoordinating anion PF 6 -during the glycosylation of 2-propanol with trichloroacetimidates in 1-butyl-3-methylimidazolium hexafluorophosphate [bmim]-[PF 6 ] was observed.…”
Section: Resultsmentioning
confidence: 99%
“…However, whereas triflate-based ionic liquids induced β-selectivity (presumably by coordination of the triflate counterion on the α-face of the glycosyl donor), no influence of the hydrophobic, noncoordinating anion PF 6 -during the glycosylation of 2-propanol with trichloroacetimidates in 1-butyl-3-methylimidazolium hexafluorophosphate [bmim]-[PF 6 ] was observed. [14] The stereochemistry of the product www.eurjoc.orgwas dependent on the anomeric configuration of the donor, with an inversion of the configuration with low selectivity usually being reported. From supported disaccharides 10, we developed a second α-(1Ǟ4)-glycosylation reaction with two new acceptors, 16 and 17.…”
Section: Resultsmentioning
confidence: 99%
“…Room temperature ionic liquids have attracted significant attention of synthetic chemists for their capability to act as green reaction medium as well as organo-catalyst [27][28][29][30][31][32][33][34][35]. In the recent past, several organic transformations have been carried out in the ionic liquids under green reaction conditions [36][37][38][39][40][41][42][43]. Earlier, Salunkhe et.…”
mentioning
confidence: 99%